2000
DOI: 10.1080/010503900424570
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacusis: Case studies and evaluation of electronic loudness suppression devices as a treatment approach

Abstract: Hyperacusis, as defined here, is a relatively rare condition in which the patient, with or without hearing loss, experiences severe loudness discomfort to everyday environmental sound levels. The case studies of 14 patients with severe hyperacusis are described; all wore passive attenuators (earplugs and/or earmuffs) in an attempt to alleviate their discomfort, frequently producing communication difficulties. These subjects were fitted binaurally with experimental electronic loudness suppression devices housed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
2
12
1
1
Order By: Relevance
“…Thirty-eight per cent of patients with CRPS related dystonia in our study reported hyperacusis, whereas the prevalence of hyperacusis in the general population is less than 2% 16. Auditory function, evaluated by means of the PTT and SRT, showed no differences between patients and the general population.…”
Section: Discussioncontrasting
confidence: 63%
“…Thirty-eight per cent of patients with CRPS related dystonia in our study reported hyperacusis, whereas the prevalence of hyperacusis in the general population is less than 2% 16. Auditory function, evaluated by means of the PTT and SRT, showed no differences between patients and the general population.…”
Section: Discussioncontrasting
confidence: 63%
“…This incongruence was already previously seen when comparing subjective benefi t and benefi t in DR in a study investigating loudness suppression devices. (Sammeth et al, 2000) Moreover, this is also in line with tinnitus complaints, in which perceived tinnitus loudness and annoyance were shown to be not or only moderately related. (Folmer et al, 1999;Hiller & Goebel, 2006) Conclusion No correlation was found between patients' complaints of hyperacusis and ULL or DR measurements.…”
Section: Comparison Of Hyperacusis Measurement Toolssupporting
confidence: 69%
“…Entsprechend divergieren auch die wenigen vorhandenen epidemiologischen Angaben anderer Länder: So fand Fabijanska 1999 bei 15,2% der polnischen Bevölkerung eine Hyperakusis [4],während die American Tinnitus Association [24] dies "nur" für etwa 2% ermittelte. Dabei beruht die auffällige Diskrepanz mit großer Sicherheit auf der Unterschiedlichkeit der Definitionen,Fragestellungen und Befragungen.…”
Section: Epidemiologieunclassified